Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jsbmb.2019.105470
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and serotonin reuptake inhibitors alter placental aromatase

Abstract: Serotonin reuptake inhibitors (SRIs) are currently the main molecules prescribed to pregnant women that suffer from depression. Placental cells are exposed to SRIs via maternal blood, and we have previously shown that SRIs alter feto-placental steroidogenesis in an in vitro co-culture model. More specifically, serotonin (5-HT) regulates the estrogen biosynthetic enzyme aromatase (cytochrome P450 19; CYP19), which is disrupted by fluoxetine and its active metabolite norfluoxetine in BeWo choriocarcinoma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…Prenatal SSRI exposure also tends to be associated with lower fetal-placental weight ratios and fetal vascular malperfusion, indicative of less efficient fetal blood flow to or from the placenta (22). Both of these factors indicate less efficient placental function in association with prenatal SSRI exposure, which may be related to downstream neonatal cognitive outcomes (22); SSRI exposure on the placenta has been previously reported to affect syncytializaton and extravillous trophoblast function, and to affect placental 5-HT levels (2325). Taken together, the effect of SSRI exposure on pregnancy outcomes suggests an interplay between the placenta and SSRI pharmacobiology, which could occur by a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal SSRI exposure also tends to be associated with lower fetal-placental weight ratios and fetal vascular malperfusion, indicative of less efficient fetal blood flow to or from the placenta (22). Both of these factors indicate less efficient placental function in association with prenatal SSRI exposure, which may be related to downstream neonatal cognitive outcomes (22); SSRI exposure on the placenta has been previously reported to affect syncytializaton and extravillous trophoblast function, and to affect placental 5-HT levels (2325). Taken together, the effect of SSRI exposure on pregnancy outcomes suggests an interplay between the placenta and SSRI pharmacobiology, which could occur by a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these factors indicate less efficient placental function in association with prenatal SSRI exposure, which may be related to downstream neonatal cognitive outcomes 14 . Exposure to maternal SSRI treatment has previously been reported to affect syncytializaton of placental trophoblasts and extravillous trophoblast function, and to affect placental serotonin levels [15][16][17] . Taken together, the effect of SSRI exposure on pregnancy outcomes suggests an interplay between the placenta and SSRI pharmacobiology, which could occur by a variety of mechanisms.…”
mentioning
confidence: 99%
“…One more role assigned to the HTR2A receptor in the human placenta relates to the regulation of placental estrogen production. Specifically, studies in human primary trophoblasts ( 106 ) as well as trophoblast-like cell lines (BeWo, JEG-3) ( 107 ) have shown that serotonin induces the expression and activity of aromatase CYP19, a key enzyme in placental estrogen synthesis, via activation of the HTR2A receptor. The observed increase in aromatase activity was induced by HTR2A-mediated stimulation of the protein kinase C pathway ( 107 ) and possibly the JAK2/STAT3 pathway ( 104 ).…”
Section: Serotonin System and Its Components In The Human Placentamentioning
confidence: 99%
“…Furthermore, studies in animals and humans suggest an interaction between sex hormones and the serotonin system. For example, estrogens modulate the synthesis, uptake and catabolism of serotonin ( 147 ), while changes in serotonin signaling have been reported to affect estrogen production ( 106 , 148 ). Overall, the influence of fetal sex needs to be considered in future studies of the function, regulation, and pathology-related changes of the serotonin system in the human placenta.…”
Section: Outlook - Future Perspectivesmentioning
confidence: 99%